Combined Intravenous Sildenafil and l-Arginine Administration in a Porcine Animal Model: Hemodynamic Safety Profile and Effects on Coronary Blood Flow - Marek Brzezinski; Gabriela R. Dincheva; Kelsey Alloo; Celeste Wong; Chun-Miao Feng; Wynnis L. Tom; Ali Salahieh; Arthur W. Wallace (Adis, Springer Healthcare, 2020)
Abstract Background Endothelial dysfunction in the nitric oxide-cyclic guanosine monophosphate pathway is a potential contributor to perioperative myocardial ischemia. The nitric oxide precursor, l-arginine, and the cyclic guanosine monophosphate degradation blocker, sildenafil, have vasodilatory effects under high dosage. Objective This study examined the hemodynamic safety and effect profiles of the combined administration of l-arginine and sildenafil using an in-vivo pig model. Methods Hemodynamic safety including mean arterial pressure, central venous pressure, heart rate, coronary vascular resistance, and systemic vascular resistance, as well as effect profiles including cardiac output and left anterior descending blood flow were measured in ten female swine after administrations of l-arginine, sildenafil, as well as combined l-arginine and sildenafil. Measurements were compared using repeated-measures analysis of variance and linear mixed models. Results The combination of l-arginine and sildenafil produced a significant dose-dependent increase in left anterior descending flow and cardiac output. In contrast, mean arterial pressure, heart rate, central venous pressure, coronary vascular resistance, and systemic vascular resistance did not show any significant changes. No significant change in serum osmolality was observed after administrations of l-arginine. Conclusions The combined intravenous administration of sildenafil and l-arginine in a porcine animal model was safe, well tolerated, and had at least additive effects on left anterior descending artery blood flow. Simultaneous application of both drugs might have dose-sparing effects leading to desired coronary effects at lower and safer sildenafil and l-arginine plasma concentrations. Hyperosmolality was only a minor factor in l-arginine hemodynamic effects.